Expressive suppression moderates the relationship between PTSD from COVID-19 and somatization and validation of the Arabic version of Patient Health Questionnaire-15 (PHQ-15). - Antonio Nehme; Sara Moussa; Feten Fekih-Romdhane; Ecem Yakın; Souheil Hallit; Sahar Obeid; Georges Haddad (PLoS ONE, 2024)
Background Lebanese adults have been crippled for years by several crises, including the lately COVID-19 pandemic. These massive civilian traumas have increased the risk of post-traumatic stress disorder (PTSD) in this population. Extensive literature pointed to the association between PTSD and somatization; however, the nature of this relationship remains unknown. We sought to contribute further to work in this area by testing the moderating role of emotion regulation in the relationship between COVID-19- related PTSD and somatization. As a secondary objective, we aimed to examine the psychometric properties of an Arabic translation of the somatization measure Patient Health Questionnaire-15 (PHQ-15) in terms of factorial validity and internal consistency before its use in the present study. Methods This cross-sectional study was conducted between September and October 2021. A total of 403 Lebanese adults residing in Lebanon were recruited. Eligible participants received an online link to the survey. The Patient Health Questionnaire-15 was used to assess somatization, PTSD Checklist-Civilian Version for PTSD and Emotion Regulation Questionnaire for emotion regulation. Results The results of the exploratory factor analysis (EFA) revealed a three-factor solution explaining 48.79% of the common variance. Confirmatory Factor Analysis results of the three-factor model obtained in the EFA indicated a good fit with a significant CFI of 0.98, TLI 0.98 and a GFI of .97, a RMSEA of .04 [90% CI .01, .06]. Higher PTSD symptoms were associated with somatization. In addition, we found that one specific ER component, i.e. expressive suppression, significantly moderated the relationship between PTSD from the COVID pandemic and somatization. In particular, the interaction PTSD from the COVID-19 pandemic by expressive suppression was significantly associated with somatization; at low, medium and high levels of expressive suppression, higher PTSD from the COVID-19 pandemic was significantly associated with higher somatization scores. As for our secondary objective, findings revealed that the Arabic version of the PHQ-15 exhibited good psychometric properties. In particular, the scale yielded a three-factor structure, and good internal consistency (Cronbach's alpha = 0.87). Conclusion The moderating role of expressive suppression on the link between PTSD and somatization presents a novel finding in the field of trauma. Additionally, making a psychometrically sound Arabic version of the PHQ-15 available is a valuable addition to the literature.